Assessing physiotherapists' communication skills for promoting patient autonomy for self-management: reliability and validity of the communication evaluation in rehabilitation tool. Issue 14 (3rd July 2019) - Murray, Aileen; Hall, Amanda; Williams, Geoffrey C.; McDonough, Suzanne M.; Ntoumanis, Nikos; Taylor, Ian; Jackson, Ben; Copsey, Bethan; Hurley, Deirdre A.; Matthews, James
Abstract: Purpose: To assess the inter-rater reliability and concurrent validity of the Communication Evaluation in Rehabilitation Tool, which aims to externally assess physiotherapists competency in using Self-Determination Theory-based communication strategies in practice. Materials and methods: Audio recordings of initial consultations between 24 physiotherapists and 24 patients with chronic low back pain in four hospitals in Ireland were obtained as part of a larger randomised controlled trial. Three raters, all of whom had Ph.Ds in psychology and expertise in motivation and physical activity, independently listened to the 24 audio recordings and completed the 18-item Communication Evaluation in Rehabilitation Tool. Inter-rater reliability between all three raters was assessed using intraclass correlation coefficients. Concurrent validity was assessed using Pearson's r correlations with a reference standard, the Health Care Climate Questionnaire. Results: The total score for the Communication Evaluation in Rehabilitation Tool is an average of all 18 items. Total scores demonstrated good inter-rater reliability (Intraclass Correlation Coefficient (ICC) = 0.8) and concurrent validity with the Health Care Climate Questionnaire total score (range: r = 0.7–0.88). Item-level scores of the Communication Evaluation in Rehabilitation Tool identified five items that need improvement. Conclusion: Results provide preliminary evidence to support future use and testing of the Communication Evaluation in Rehabilitation Tool. Implications for Rehabilitation: Promoting patient autonomy is a learned skill and while interventions exist to train clinicians in these skills there are no tools to assess how well clinicians use these skills when interacting with a patient. The lack of robust assessment has severe implications regarding both the fidelity of clinician training packages and resulting outcomes for promoting patient autonomy. This study has developed a novel measurement tool Communication Evaluation in Rehabilitation Tool and a comprehensive user manual to assess how well health care providers use autonomy-supportive communication strategies in real world-clinical settings. This tool has demonstrated good inter-rater reliability and concurrent validity in its initial testing phase. The Communication Evaluation in Rehabilitation Tool can be used in future studies to assess autonomy-supportive communication and undergo further measurement property testing as per our recommendations.